Historicizing the Knowledge Commons: Open Access, Technical Knowledge, and the Industrial Application of Science. Issue 1 (28th February 2019) - Martin, Shawn
How does open access relate to scholarly communication? Though there are many modern definitions stressing the accessibility of knowledge to everyone, sharing scientific knowledge has a much longer history. What might the concept of 'open access' have meant to scientists and knowledge practitioners over the past several hundred years? This paper poses some relevant questions and calls for better historicization of the idea of the knowledge commons at different periods of time, particularly the era of the 'Republic of Letters' and the 'Modern System of Science.' The concept of open access as it relates to academic publishing has been very nuanced, and hopefully, understanding the history of 'open access' in relation to scholarly communication can help us to have more informed debates about where open access needs to go in the future.